The song of the nightingale : a Hawkenlye mystery - Clare, Alys (Clare, Alys. Hawkenlye mystery, 2012)
Winter, 1211. King John's reign is harsh, and his tax collectors wring money from people near to starvation. Homeless, desperate men are reduced to walking the streets, begging for handouts, and the nuns at Hawkenlye Abbey, now under John's iron rule, are all but powerless to help. Former abbess Helewise decides to move back to her cell near the abbey, to better help the needy, putting a strain on her tentative relationship with Sir Josse D'Acquin. But he must put his personal feelings aside when he is called examine the body of a man who bears a complicated symbol carved into his chest: a symbol that signifies vengeance. Meanwhile, far from home, Josse's son Ninian has become involved in the lives and cause of the doomed Cathar people.